2021
DOI: 10.1111/jan.14943
|View full text |Cite
|
Sign up to set email alerts
|

The process of transitioning for the transgender individual and the nursing imperative: A narrative review

Abstract: Aims The objectives of this study were to bring the experience of the transitioning process for the transgender population to the nursing profession and address the lack of knowledge to promote improved patient outcomes. Design This study used a narrative review using the literature matrix method. Because of the dearth of trans specific literature, editorials and monologues were included. Data source A broad search was undertaken across all databases including CINAHL, PubMed, PsycINFO, Ovid MEDLINE, ProQuest N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Additional assessment can offer the TGD person an opportunity to consider the possible effects of not socially transitioning while still obtaining GAMSTs. Given the lack of data on health outcomes for TGD people who do not socially transition (Evans et al., 2021 ; Levine, 2009 ; Turban, Loo et al., 2021 ), GAMSTs should be approached cautiously in such circumstances.…”
Section: Chapter 5 Assessment Of Adultsmentioning
confidence: 99%
“…Additional assessment can offer the TGD person an opportunity to consider the possible effects of not socially transitioning while still obtaining GAMSTs. Given the lack of data on health outcomes for TGD people who do not socially transition (Evans et al., 2021 ; Levine, 2009 ; Turban, Loo et al., 2021 ), GAMSTs should be approached cautiously in such circumstances.…”
Section: Chapter 5 Assessment Of Adultsmentioning
confidence: 99%
“…Although they are far from comprehensive, the broad terms trans and nonbinary are the ones usually used in scholarly journals that publish in English. However, gender-related language and terminology continue to evolve within TNB communities 23 . We encourage readers who want to learn about current language and terms to regularly search the scholarly literature (such as ref.…”
Section: Introductionmentioning
confidence: 99%
“…We encourage readers who want to learn about current language and terms to regularly search the scholarly literature (such as ref. 23 ) and to review recent discussions in public TNB social media groups.…”
Section: Introductionmentioning
confidence: 99%
“…Making sure there are places where people feel comfortable expressing their culture freely is also crucial to ensuring their safety. Evans et al [4] found that patients' mental well-being and satisfaction with care improved when they were given opportunities to discuss their cultural identities and beliefs. Rapport and trust building have been extensively researched as crucial components of cultural safety in healthcare settings [5].…”
Section: Understanding Cultural Safetymentioning
confidence: 99%